The Concept of Extending Tradition Majapahit’s Architecture in Mojokerto Hybrid Community Center - Mubarak, M. Husni; Sekarningtyas, Rizadewi Nurul Amalina; Handryant, Aisyah Nur (Proceedings of the International Conference on Green Technology; Vol 9 No 1 (2018): Proceeding of the 9th International Conference on Green Technology 2018DO - 10.18860/icgt.v9i1.850, 2019)
The city of Mojokerto is an area with a high population density. The high population density of Mojokerto City is not matched by the amount of city public space, both in the form of green open spaces and non-green open spaces. The city of Mojokerto has cultural potential, local products, culinary, and traditional arts that are still less exposed due to lack of marketing. This study aims to provide design ideas in the form of site, spaces and forms concept in public open space facilities that accommodate function of social, cultural-educational, and recreational with an extending tradition approach design to introduce the characteristics of Majapahit architecture. This study uses a qualitative method with the initial steps to find primary data in the form of observation studies (site, climate, and environmental data) and secondary data (study of object and approach literature). Then the data is analyzed by the linear method in the form of analysis of function, space, site and form. The design concept (site, space and form) is obtained from the results of the analysis with the principles of the Extending Tradition approach. The results of this study are suggestions of design concepts in the form of site, spaces, and forms concepts that are applied in the Mojokerto Hybrid Community Center design in the hope of answering the needs of the people of Mojokerto City for public spaces that carry the characteristics of Majapahit architecture.